Intramyocellular lipids of muscle type in athletes of different sport disciplines - Nakagawa, Y.; Hattori, M. (Open Access Journal of Sports Medicine, 2017)
The present study used magnetic resonance spectroscopy (1H-MRS) to examine quantitative differences in intramyocellular lipid (IMCL) contents in various muscle types at rest for individual athletes from different sport disciplines. Five groups consisting of sprinters, alpine skiers, cross-country skiers, endurance runners and untrained healthy male subjects volunteered for this study. Data were acquired using 1H-MRS from the tibialis anterior (TA), medial gastrocnemius (MG) and soleus (SOL) muscles. No significant difference was found in the cross-sectional area (CSA) of the TA, MG and SOL muscles, whereas the CSA of subcutaneous fat was significantly lower (p<0.01) for each athlete group compared with untrained subjects. In both TA and MG, IMCL concentrations in endurance runners were significantly higher than those of alpine skiers (p<0.01), sprinters (p<0.01) and untrained subjects (p<0.05). The IMCL concentrations in TA and MG of cross-country skiers were significantly higher than those of alpine skiers (p<0.05) and sprinters (TA, p<0.01; MG, p<0.05). There was no significant difference in the IMCL concentrations of TA and MG between alpine skiers or sprinters and untrained subjects. The IMCL concentration in SOL was significantly greater in endurance runners and showed no difference in cross-country skiers compared with that in alpine skiers and sprinters. There was no significant difference in the IMCL concentration of SOL between athletes and untrained subjects. These results suggest that differences in IMCL contents stored in various muscle types for athletes at rest are associated with the muscle cellular adaptation for differences in the type of exercise training and/or muscle fiber composition.